2002
DOI: 10.1002/mds.1261
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem analysis of bilateral subthalamic electrode implants in Parkinson's disease

Abstract: This is the second neuropathological report detailing bilateral electrodes targeting the subthalamic nucleus (STN) in idiopathic Parkinson's disease (PD). The patient presented with unilateral tremor-dominant parkinsonism. Bilateral STN stimulation was carried out 7 years later due to significant disease progression and severe motor fluctuations. The patient exhibited bilateral improvements in rigidity and bradykinesia both intraoperatively and postoperatively. The patient died 2 months later from aspiration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 35 publications
7
78
0
1
Order By: Relevance
“…Reports examining the postmortem brain parenchyma around a DBS electrode in subcortical targets long after implantation have concluded that no serious histopathological complications are seen after chronic electrical stimulation irrespective of the amount of stimulation [3,[5][6][7][8]. For example, Burbaud et al [8] found focal astrocytic gliosis and mild leukocytic infiltration in the chronic track of two bilateral DBS electrodes implanted about 2 years before death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports examining the postmortem brain parenchyma around a DBS electrode in subcortical targets long after implantation have concluded that no serious histopathological complications are seen after chronic electrical stimulation irrespective of the amount of stimulation [3,[5][6][7][8]. For example, Burbaud et al [8] found focal astrocytic gliosis and mild leukocytic infiltration in the chronic track of two bilateral DBS electrodes implanted about 2 years before death.…”
Section: Discussionmentioning
confidence: 99%
“…There have been five autopsy studies on patients treated with DBS to assess the long-term effect of stimulation electrodes on brain tissue [3,[5][6][7][8]. In the largest of these, 8 postmortem brains of patients with DBS implanted for Parkinson's disease all had well-preserved neural parenchyma with only mild gliosis around the lead track, compatible with reactive changes due to surgical placement of the electrode [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such absence of permanent sequelae as well as location of edema isolated at the tip, perilead or subcortically makes it unlikely to be due to a venous infarct, which has typical imaging characteristics showing cortical wedge-shaped ischemia [1,10]. Very likely, mechanical trauma due to microelectrode and DBS lead insertion disrupts the blood-brain barrier to some extent, which could result in the possibility of “luxury perfusion” [1,2,15]. Why this leads to such clinical presentations seen in a small subset of patients herein is curious, as it is unclear why such an occurrence remains predominantly unilateral despite bilateral implantation, here and in other series [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…The study of patients with early disease is warranted to explore the hypothesis that brain change starts early in the disease; a finding which if confirmed would warrant a change in proposed treatment paradigms. The basal ganglia and the globus pallidus in particular are key regions of the brain with associated pathophysiology in a variety of conditions ranging from movement disorders, such as Parkinson's disease 14 to chronic hepatitis C, and in manganese workers, who have been exposed to industrial pollution. [15][16][17] It has been previously hypothesised that disrupted activity in these areas of the brain leads to decreased motivation in these conditions, perceived by the individual as fatigue.…”
Section: Introductionmentioning
confidence: 99%